Value hierarchy for Massive Open Online Courses. (December 2015) - Lin, Yu-Ling; Lin, Hong-Wen; Hung, Tzu-Ting
Highlights: Explores learners value ladder of Attributes–Consequences–Values chain in MOOCs. Laddering interviews identify 14 attributes, 12 consequences, 9 values of MOOCs. The structures of values are set up by hierarchical value map. The study further explored the difference in values in different groups. Abstract: With E-learning emerging as an important application for education, Massive Open Online Courses (MOOCs) have further sparked a trend of online higher education learning. In order to explore the target values that learners pursue through MOOCs, this study adopted Means-end Chains theory and laddering interview to examine the structure of MOOCs' "Platform Attribute–Learning Consequences–Terminal Values" through learners' perspective. The study found that through platform attributes of Rich course contents, Real-time discussion platform, Video instruction and Qualifications, learners were able to benefit from the learning consequences of Enhanced understanding of knowledge, Facilitation of learning exchanges and interactions, Ease of time management and Improve competitiveness, thereby delivering the terminal values of Fun and enjoyment of life, Self-fulfillment and Sense of achievement . The study also took a further step to examine the discrepancies between user groups of different experience and number of courses completed and found that users in different groups emphasized on different attributes. In addition, the study also offered suggestions pertaining to management and education implications. Results of the study should not only enable platform designers to become more effective in the development process but also enable teachers to develop teaching guidelines that will effectively boost learners' motivations so as to further refine the MOOCs learning environment.